Epidemiological surveillance of blood donors at the University Clinics of Kinshasa, Kinshasa, DR Congo (2019–2022) - Olivier Lomamba Lodi; Blaise S. Matondo; Yvette N. Ndona; S. Melki; Jonathan K. Ibana; Franck N. Lukusa (Orapuh Journal)
Introduction